Capital Budgeting Model and Sensitivity Analysis of the Conventional Oil Production Sharing Contract (PSC) Fiscal Systems: Empirical Evidence from Indonesia - Mardawiyah Daryanto, Wiwiek; Primadona, Arti; ., . (International Journal of Engineering and Technology, 2018)
Oil is a vital commodity that controls the livelihood of people. It is also the main resource of state revenue. The oil industry in Indonesia has started since 1883. However, only 40 percent of the total sedimentary basin in Indonesia has been explored since that time (Ministry of Energy and Mineral Resources of Republic of Indonesia, 2015). Accordingly, the major fields are getting drain, while the domestic consumption of oil is increasing. Low investment is one of the factors that cause the declines of oil production. Working Areas (WA) which had been offered to the potential investors by the Government of Indonesia (GOI) during the period ended September 10, 2015, were unsold, followed by unsuccessful of seven WAs offered in the period from July 18 to October 28, 2016, due to an unattractive terms and conditions of PSC Fiscal Systems in the decreasing of oil price situation currently. Oil business requires high capital, high technology, high risks, long terms commitment, but high returns. Therefore, GOI always depends on the private investor to run exploration and exploitation of oil mining. The purpose of this study is to measure the feasibility of oil industry investment and to examine the attractive terms and conditions of PSC Fiscal Systems. The data were collected from the ten PSC Fiscal Systems which had been started the business since 1968 - 2014. Capital Budgeting Model indicators: Payback Period, Net Present Value (NPV), Internal Rate of Return (IRR), and Weighted Average Cost of Capital (WACC) were used to analyze the data and sensitivity analysis. The finding shows that the attractive terms and conditions of PSC Fiscal Systems are a maximum split of 50 percent for GOI, under controllable Cost Recovery (CR), the oil price of USD 50.00/barrel, and WACC <20%. The authors believe that the findings will be beneficial for GOI and potential oil investors to carry out a fair negotiation, to come up with a win-win solution.Â Â